(3OQQ GdMcGe aj TQM ZQQ GdCMcGes - (3edG NSQh, eMeO Hf aQGehR Hf Ydj, J (B885 (3g`s ((3bQjI CeQ GdSdWGfs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj CMce CMcGe GdTQY Gdbhje hNU HYO fHjge faQG HEYdGA CbOGQge hefGUHge EP Ydi CbhGdge eOGQ GdCMcGe hNU efge GdEeGe GdCYXe CHG MfjaI fYeGf Hf KGHJ hYGReG Cf CSejJg HYO JeGe GdEJeGe OQQ GdMcGe aj TQM ZQQ GdCMcGe (B--s
(3BNQgG (B:s
(3hEfeG jMJGL Edi aSN GdMGce dCf GdhUj dh YRe JQc GdNUheI cGf aSNgeG HefRdI GdEbGdI ajdRe GdhUj ceG dh JbGHdG MbjbI aEPG aSN GdbGVj de jcf EbGdI adG jdRe GdhUjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 328s
(3eYLe GdeDdajf (B3 / 584s
(3cTa GdXfhf (B2 / 1199s
(3TPQGJ GdPgH (B7 / 342s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs